Vehicular Ad-hoc Network & Exploration Plugs - Jaiswal, Kriti Vishesh; Sharma, Santosh Kumar; Verma, Ravindra Kumar; Singh, Brijesh Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Different sorts of networks can now be implemented in a variety of settings thanks to recent developments in communication technology. VANET, which stands for Vehicular Ad-Hoc Network, is a specific type of network. It falls under the category of Mobile Ad-Hoc Networks (MANET) and presents unique challenges as it enables smart communication between vehicles and infrastructure. Vehicular Ad-Hoc Network (VANET) presents a highly promising approach for the implementation of Intelligent Transport Systems (ITS), as evidenced by extensive research in this field. Since a few years ago, VANET has drawn more interest as a viable technology to improve both comfort and active and preventive safety on the road. Finding and maintaining a reliable path for data transmission is one of the primary issues facing VANET. In the midst of moving vehicles at high speeds, communication must be dependable, constant, and seamless.